Analisis Faktor Pengaruh Pemilihan Kereta Api Sebagai Moda Transportasi - Purnomo Ari Wibowo; Ngaijan Ngaijan; Andar Sri Sumantri; Supriyanto Supriyanto (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
This research was conducted with the aim of knowing the partial and simultaneous effect of accessibility, effectiveness, promotion, and trust on passengers' decisions in choosing the Kamandaka Train. The population in this study were Kamandaka train passengers. The sampling technique used is non-probability sampling with the type of sampling that is incidental sampling. The analytical method used is descriptive analysis. Data were analyzed using multiple linear regression analysis with the help of Software Statistical Package For Social Science (SPSS) version 25. The results of this study indicate that the variables Accessibility, Effectiveness, Promotion, and Trust have a partial and simultaneous effect on Passenger Decisions. The results of multiple linear regression analysis obtained the equation Y = -2.766+ 0.357.X1 + 0.322.X2 + 0.181.X3 + 0.352.X4 + µ. The results of the equation show that the accessibility variable has a positive and significant effect on passenger decisions (tcount 4.155 > ttable 1.98498), effectiveness on passenger decisions (tcount 3.258 > ttable 1.98498), promotion of passenger decisions (tcount 2.036 > ttable 1.98498 ), Trust in Passenger Decisions (tcount 4.750 > ttable 1.98498) As for the value of Adjusted R2 = 0.577. This means that 57.7% of the variation in the dependent variable (Y), namely Passenger Decisions, is explained by the independent variables, namely Accessibility, Effectiveness, Promotion, and Trust. The remaining 100% - 57.7% = 42.3%, influenced by other variables outside the research.